Tourism Communication Model Based on Local Wisdom on Lombok Island, West Nusa Tenggara - Dela Rahayu; Fauziah Yanis (Eduvest - Journal of Universal Studies, 2023)
Local wisdom currently has an attractiveness and selling value which is used as a tourism object that tourists want to enjoy. Existing cultural values ​​can bring benefits both socially and economically. Local wisdom that is well packaged through tourism communication can form a Local Branding. This research focuses on local wisdom in several tourist destinations on Lombok Island, West Nusa Tenggara. The method used in this research is descriptive qualitative with direct observation data collection techniques and literature study. The results of this study indicate that an effective tourism communication model used to increase local wisdom is a multi-step communication model, by combining several communication models such as interpersonal, persuasive and mass communication. In order to continue to run effectively, there is a need for sustainable (sustainable) commitment and cooperation between related parties in the tourism sector.